A novel KRAS mutation in metastasic conjunctival melanoma: a case report and literature review. Issue 2 (April 2018) - Del Carpio Huerta, Luis P.; Mas Castells, Maria; Anguera Palacios, Georgia; Sullivan, Ivana; Gonzalez Vidal, Alan; Majem Tarruella, Margarita
Abstract : Conjunctival melanoma is a rare disease, and little is known about its molecular background. Here, we present the case of a 48-year-old patient with conjunctival melanoma and metachronic lymph node and skin metastasis with KRAS p.K117Y mutation in exon 4 in all the lesions. The cancer genome interpreter predicted this mutation to have driver function. To our knowledge, this is the first time this mutation is found in conjunctival melanoma. An important role in the disease development is suggested. Abstract : Supplemental Digital Content is available in the text.